'The clamour of Babel, in all the tongues of the Levant': multivernacular and multiscriptal Constantinople around 1900 as a literary world. Issue 5 (3rd May 2020) - Bodin, Helena
ABSTRACT: With a focus on the crafting of Constantinople as a literary world, this article considers how the city's particularly rich and composite soundscape, linguascape and scriptworld around 1900 contributes to a vernacular poetics. Such a poetics, I suggest, could be described in terms of a heterolingual and multivernacular foregrounding of linguistic difference and asymmetry. Issues relating to the materiality of language and linguistic diversity, including the role of scripts, are explored in a selection of ten Western European travelogues and narratives set in Constantinople during the last period of the Ottoman era (1876–1922) and written in Italian (De Amicis), French (Loti), Danish (Jerichau-Baumann), Norwegian (Skram), and Swedish (Lindberg-Dovlette and Beyel). Proceeding from the soundscape via the linguascape to the scriptworld of the city, it is demonstrated how these '-scapes' and worlds are established, rendered, thematised, transcribed, and inscribed as heterolingual, multivernacular and multiscriptal in Constantinople as a literary world. Different textual and paratextual strategies are identified and analysed with regard to their auditory, visual and material features. However, as a part of monoscriptal Western European literature using Roman script, this literary world becomes cosmopolitanised. In this case the vernacular poetics did not embrace the many scripts of Constantinople.